Analisis Dampak Penayangan Film 5 CM sebagai Media Komunikasi terhadap Sektor Pariwisata di Kawasan Gunung Semeru - Devista Tria Ananda; Arsya Amala Rosyada; Eva Zahra Hayunda Abadi; Fina Rifa’Tun Nami; Alea Syafa Alfarelia; Arsih Amalia Chandra Permata; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
The tourism sector is a strategic industry that plays a significant role in economic development. One of the most effective forms of tourism promotion is through film media. This study aims to examine the impact of the film 5 cm on the tourism sector in the Mount Semeru area. The research method used is descriptive qualitative with data collected through literature studies. The results indicate that the screening of the film 5 cm had a significant influence on the increase in tourist visits. Moreover, the film also affected tourists’ motivation to visit Mount Semeru. However, the surge in visitors following the film's release has led to various challenges, such as increased waste generation, pressure on environmental carrying capacity, and potential conflicts between conservation efforts and tourism activities. This study concludes that film-based promotion must be accompanied by sustainable tourism management to ensure that economic benefits do not come at the expense of environmental preservation..